Discursos sobre a violência contra a mulher no dark romance: uma análise de enunciados da plataforma X - Matos, Julia de Oliveira (Universidade Federal de São Carlos, 2025)
This study focuses on the analysis of enunciations taken from the platform X that discuss books from the dark romance subgenre. The central question to be debated is how these enunciations address the violence against women present in such content. The general objective of the research was to discuss how violence and male domination are perpetuated in dark romance books and in the enunciations of the readers’ community. More specifically, the study aimed to: (a) examine the discourses mobilized by these enunciating subjects; and (b) investigate whether gender-based violence is perpetuated in their statements or whether these statements discursively resist it. The research was conducted through an inductive approach, seeking to generate broader reflections from small analytical fragments. As it aims to explain issues related to the perpetuation of violence within a literary genre that remains understudied, the research can also be considered exploratory. The analyses revealed a strong discursive movement of denunciation regarding the crimes committed against women in romantic novels, as well as an attempt to regulate representations of love by defining which narratives deserve to be consumed, which should be repudiated, and which moral and psychological effects are attributed to each choice that renders domination as something beautiful or “aesthetic”.
Discurses on violence against women in dark romance: an analysis of statements from platform X
Keywords: Discurso; Violência de gênero; Dark romance; Livros; Plataforma X; Discourse; Gender violence; Books; Platform X; LINGUISTICA, LETRAS E ARTES::LINGUISTICA; 4. Educação de Qualidade